The Influence of Environmental Management System and Environmental Performance on Financial Performance With Environmental Innovation as A Mediating Variable (Hospital and Healthcare Company in Jakarta) - Eko Oktavianus (PT Keberlanjutan Strategis Indonesia, 2024)
Global warming and ozone depletion are acknowledged as significant environmental challenges, positioning environmental management systems as a central emphasis in endeavors to safeguard the environment. This also becomes the focal point for a business in executing its operational activities that can influence its financial performance. This study seeks to evaluate the influence of the Environmental Management System and Environmental Performance on Financial Performance, with Environmental Innovation acting as a mediating variable. This study utilizes a quantitative approach that includes the dissemination of questionnaires and a comprehensive literature evaluation for reference enhancement. The findings of this study demonstrate that Environmental Innovation, Environmental Management Systems, and Environmental Performance substantially improve Financial Performance. The Environmental Management System and Environmental Performance significantly enhance Environmental Innovation.